PENGGUNAAN MEDIA PEMBELAJARAN BERBASIS VIDEO PADAMATA PELAJARAN FIKIH KELAS VIII MADRASAH TSANAWIYAH SWASTA AL-ITTIHADIYAH MAMIYAI MEDAN - Haryanto, Salwa Aprilianda (Taushiah: Jurnal Hukum, Pendidikan dan Kemasyarakatan, 2020)
In line with the development of science and technology (IPTEK), especially in the field of education, the use of learning aids or media has become more extensive and interactive, such as the projector infocus media, computers and the internet. The teacher's habit of teaching with the same teaching method, such as the lecture method, the question and answer method, the assignment method, etc. and using media tools that only come from textbooks and student worksheets (student worksheets) is the background for this research. The learning objectives of Jurisprudence will be easier to achieve if the teacher adds variations in the teaching and learning process using teaching methods combined with using learning media such as video-based audio-visual media. This research is a qualitative research, with documentation and interviews with information participants from the Al-Ittihadiyah Mamiyai Medan Private Madrasah which collected information and documentation that has been collected and from that conclusions can be drawn. The results of this study indicate that video-based learning media is a learning medium that converts an idea or subject matter ideas into an image and sound display whose recording and viewing process involves certain technologies. With the existence of video-based learning media, it makes it easier for teachers to distribute the contents of Hajj pilgrimage material to students and makes it easier for students to understand the contents of the Hajj pilgrimage material. With the existence of video-based learning media can also generate enthusiasm for student learning, learning is not boring and can increase motivation, interest and achievement of student learning outcomes. In addition, it creates affective, cognitive and psychomotor abilities of students after gaining experience in learning Jurisprudence with the theme of iabadah haji using video-based learning media.